To Be Read at Dusk - Dickens, Charles, 1812-1870 (Salt Lake City, UT : Project Gutenberg, 1997)
"To Be Read at Dusk" by Charles Dickens is a haunting short story written during the late 19th century, a time characterized by the Victorian literary tradition. The narrative falls within the gothic genre, as it weaves themes of mystery, the supernatural, and psychological tension, exploring the inexplicable and the nature of belief in ghosts. The story emphasizes the engagement of different characters with their fears and uncertainties, particularly revolving around strange occurrences and their interpretations. The plot revolves around a group of couriers gathered outside a convent in the Swiss Alps, discussing eerie experiences and encounters with the supernatural. As they converse, one courier recounts the tale of a newly married English lady who becomes haunted by a dream of a mysterious man$1 (Bs face, which deeply unsettles her even as she settles into her new life. The arrival of the enigmatic Signor Dellombra$1 (Ba man strikingly similar to the figure from her dreams$1 (Bexacerbates her fears, leading to a tragic conclusion as she disappears under his influence. Throughout the story, Dickens plays with the interplay of reality and the supernatural, leaving the reader to question the boundaries between the two. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/To_Be_Read_at_Dusk
Release date is 1997-05-01
Transcribed from the 1905 Chapman & Hall edition (_The Works of Charles Dickens_, volume 28) by David Price
Keywords: Fiction; Short stories; Ghost stories